Prevalence of dyslipidemia in adolescents: comparison between definitions - Tomeleri, Crisieli M.; Ronque, Enio R. V.; Silva, Danilo R. P.; Cardoso Junior, Crivaldo G.; Fernandes, Romulo A. [UNESP]; Teixeira, Denilson C.; Barbosa, Decio S.; Venturini, Danielle; Okino, Alessandra M.; Oliveira, Jair A.; Cyrino, Edilson S. (Elsevier B.V., 2015)
Introduction: The indiscriminate use of different diagnostic criteria for the definition of dyslipidemia may result in inaccurate interpretations, which could compromise diagnosis and therefore the therapeutic and prophylactic actions to be taken.Objective: To analyze possible differences in prevalence rates of dyslipidemia in adolescents based on three diagnostic definitions.Methods: A cross-sectional study was conducted of a representative sample of Brazilian adolescents between 11 and 16 years of age. Blood samples were collected from 1000 students (423 boys and 577 girls) to determine fasting total cholesterol (TC), HDL and LDL cholesterol, and triglycerides (TG). The prevalence of dyslipidemia was established according to three definitions: those of the National Cholesterol Education Program (NCEP), the Brazilian Society of Cardiology (BSC), and the National Health and Nutrition Examination Survey (NHANES).Results: Significant differences (p<0.01) were found between the diagnostic criteria for TC (BSC 38.3%; NCEP 11.2%; NHANES 4.8%), HDL cholesterol (BSC 30.0%; NCEP 15.8% NHANES 18.4%), LDL cholesterol (BSC and NCEP 10.8% and NHANES 5.9%), and TG (BSC and NCEP 4.7% and NHANES 1.3%). The overall prevalence of dyslipidemia was 61% (BSC), 28.6% (NCEP) and 24.2% (NHANES). Agreement rates varied significantly (kappa 0.15-0.90).Conclusions: Although a high prevalence of dyslipidemia was observed in this study regardless of the diagnostic criteria used, the wide variation in rates highlights the need to establish a single definition with appropriate discriminatory power for adolescents. (C) 2014 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Risk factors; Cardiovascular disease; Atherosclerosis; Youth